Social Life of Scavengers in The Sukawinatan Landfill in Palembang, Indonesia - Diana Dewi Sartika; Vieronica Varbi Sununianti; Tri Agus Susanto (Pencerah, 2021)
Scavengers is one of the marginal communities in urban areas, including in Palembang City. The presence of scavengers in this city is illegal, because it is considered to interfere with the activities of the management, which is authorized to manage waste at the Sukawinatan Landfill, Palembang. This case study research is concerned to discern at the social life, threats and opportunities of the scavenger community in Sukawinatan Landfill. This study is conducted to determine strategic steps for improving the scavengers' life in the future. This study is carried out qualitatively. Therefore, in-depth interviews, observation and documentation are used as a way of collecting data. In-depth interviews were conducted to scavengers, informal leader and also the stakeholders. Data is analyzed through reduction, data presentation and making conclusion process. The results of the study indicate that the physical environment of the scavenger community is bad. Meanwhile, according to the in-depth interview and literatures review, some aspects of the social life of scavengers, actually worsen their quality of life, such as: drugs and low education. Nevertheless, there is hope that can be maximized to improve the quality of life of this community, such as: communality and kinship. The description of the scavenger social life can be used as a basis in formulating appropriate interventions for improving the quality of life in this scavenger community.